2020
DOI: 10.13189/ujer.2020.081015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Faculty Members in Developing the Patriotism amongst Their Students at Jadara University and Jerash Al Ahlia University from the Students' Point of View

Abstract: This study aimed at identifying the role of faculty members in developing a sense of patriotism amongst students at Jadara University and Jerash Al Ahlia from the students' point of view. The researchers adopted a descriptive approach. A questionnaire was used as a study tool. The study sample consisted of (707) students from both universities. The results showed that the faculty members had a very high significant role in developing a sense of patriotism among their students. The results also showed that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…According to the researcher, younger professors are more willing to use electronic technologies, and those with less experience are more receptive to technology, so they are more receptive to experimenting and introducing new things to their classes, and more convinced of the need to change the old methods of education. This study corresponds with Badarneh et al (2016) which revealed that the competences of the e-learning culture were greater among instructors with less than 5 years of experience than instructors who were between 5 and 10 years in experience. This result, however, contradicted the findings of Al-Qudah and Maqableh (2014) , who discovered that the years of experience variable has no statistical significance on the e-learning challenges (technical challenges, financial and administrative challenges, and professional challenges) that face faculty members in private Jordanian universities.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to the researcher, younger professors are more willing to use electronic technologies, and those with less experience are more receptive to technology, so they are more receptive to experimenting and introducing new things to their classes, and more convinced of the need to change the old methods of education. This study corresponds with Badarneh et al (2016) which revealed that the competences of the e-learning culture were greater among instructors with less than 5 years of experience than instructors who were between 5 and 10 years in experience. This result, however, contradicted the findings of Al-Qudah and Maqableh (2014) , who discovered that the years of experience variable has no statistical significance on the e-learning challenges (technical challenges, financial and administrative challenges, and professional challenges) that face faculty members in private Jordanian universities.…”
Section: Discussionsupporting
confidence: 86%
“…The researchers said that because scientific areas are more exposed to computers and internet applications than humanities, it is predicted that faculty members in scientific departments will have significantly superior technology abilities than their counterparts in humanitarian departments. This finding contradicted Badarneh et al (2016) , who concluded that there were no statistically significant differences in the degree of competencies (computer use competencies, network and Internet use competencies, e-learning culture competencies) held by faculty members at one of Jordan’s universities (Al-Balqa Applied University) in all areas of e-learning based on the academic department variable.…”
Section: Discussionmentioning
confidence: 78%